Wind energy planning for a sustainable transition to a decarbonized generation scenario based on the opportunity cost of the wind energy: Spanish Iberian Peninsula as case study. (January 2019) - de Simón-Martín, Miguel; de la Puente-Gil, Álvaro; Borge-Diez, David; Ciria-Garcés, Tomás; González-Martínez, Alberto
Abstract: Most countries in Europe are going under a significant transformation process from carbonized power energy sources to renewable and sustainable ones to feed their increasing demands. European Union targets on its energy roadmap states that by 2030, a reduction of 40% of CO2 emissions regarding the 1990 levels must be done and full transition must be completed by 2050. Thus, EU member countries, such Spain, are carrying out lots of investments to transform their power generation structure by promoting the installation of renewable energy power plants, with a significant visual and environmental impact. In the case of Spain, it is planned that, by 2030, 27% of final power consumption must be renewable, with approximately 31 GW of installed wind energy (8 GW must be installed in the next 10 years). Wind energy is supposed to be one of the generation leaders in this transformation context due to its high performance, high availability and fast decreasing costs. Nevertheless, wind farms have been installed on-shore with great success since the decade of the 90s covering the locations with the best wind resource. Thus, many of the installed wind turbines have overcome the half part of their expected lifespan and their payback periods, but the learning curve of the wind energy technology has improved exponentially since then. This paper is focused on the true valorization of an existing wind farm and the efficacy of the exploitation of the site's wind resource. A novel repowering decision support model based on the opportunity cost analysis between repowering the current wind farm with the latter technologies and full depletion of the wind farm is proposed and applied to the Spanish Iberian Peninsula case study. Results show that the repowering option is significantly attractive in most cases and its proper application could have, not only a positive environmental effect, but also an economic impact on the sustainability of this source of energy.